The quality of life of children with heart disease in Tanzania: a single center study - Joëlle R. Koster; Naizihijwa G. Majani; Zawadi E. Kalezi; Johanna W. Hoefnagels; Nuru Letara; Deogratias Nkya; Stella Mongela; Godwin Sharau; Sulende Kubhoja; Vivienne Mlawi; Pilly Chillo; Martijn G. Slieker; et al. (BMC Pediatrics)
Abstract Background The demand for surgical intervention for congenital heart disease (CHD) exceeds the available resources in low- and middle-income countries (LMICs). This has resulted in a growing population of children with CHD, with only few receiving surgery and many more waiting. Health-related quality of life (HRQoL) and its impact on the pediatric CHD population in these settings have been largely overlooked, and limited research has been conducted. Therefore, this study aimed to explore HRQoL in the pediatric CHD population in Tanzania by comparing unoperated and operated patients, thus bridging the knowledge gap. Methods This cross-sectional study included patients with CHD, 2 to 18 years old, without severe comorbidities, at the Jakaya Kikwete Cardiac Institute, either unoperated or operated, at least six months after cardiac surgery. Clinical and sociodemographic variables (scored 0 to 1, resp. poorest to highest) were collected. The Pediatric HRQoL Generic Core Scale (PedsQL™ 4.0 SF15, Swahili Version) provided HRQoL scores by parental report and self-report (5 years and above) for different domains (physical, social, emotional, and school). Questions were scored on a Likert linear analogue scale; higher scores indicated better HRQoL. The between-group scores were compared with Student’s t test and the Mann‒Whitney U test. Generalized linear models were used to identify predictors of HRQoL. Results Mean age of the study group was 6.3 ± 3.7 years, with a slight female predominance (n = 110, 53.9%). Operated patients had a higher socioeconomic status score (0.71/1 vs. 0.66/1) and more frequent early diagnosis (< 1 year; 67.8% vs. 47.1%). The complexity of cardiac diagnosis (simple, moderate or complex) was significantly different between groups (p = 0.001). Parent-reported HRQoL scores were significantly higher for the post-operative group (90.8 ± 10.2 vs. 80.5 ± 16.7, p < 0.001), with the most noticeable difference in the physical domain (effect size d=-0.813, p < 0.001). Being post palliative or curative surgery and higher socioeconomic status were found to be significant predictors of better HRQoL. HRQoL significantly decreased with increasing severity of heart failure symptoms. Conclusions The HRQoL of operated Tanzanian children with CHD differed significantly from that of their unoperated counterparts. Reducing symptoms for those on the waiting list can improve their HQoL. In this setting, HQoL in children with CHD is strongly predicted and influenced by socioeconomic status, emphasizing the need for interventions to address socioeconomic disparities and improve patient outcomes. Clinical trial number Not applicable.